Comparative efficacy and safety of JAK inhibitors and leflunomide in rheumatoid arthritis: A protocol for systematic review and meta-analysis. Issue 49 (9th December 2022) - Zhang, Xiaogang; Zhang, Mingming; Wang, Zhiqiang; Liu, Yanqing; Feng, Xing; Yang, Liu; Wang, Yajing; Liu, Juan; Zhao, Dongbao
Abstract : Background: Rheumatoid arthritis is the most prevalent systemic autoimmune disease among the rheumatic inflammatory musculoskeletal diseases. Currently, there is no reliable evidence regarding the comparisons of anti-rheumatic effects between leflunomide and Janus kinase inhibitors. We performed a protocol for systematic review and meta-analysis to compare the efficacy and safety of Janus kinase inhibitors and leflunomide in rheumatoid arthritis. Methods: This review has been reported following the preferred reporting items for systematic reviews and meta-analyses protocol. We will search 7 electronic databases to identify relevant studies from inception to November, 2022, which includes PubMed, MEDLINE, Embase, Cochrane Clinical Trials Database, Web of Science, China National Knowledge Infrastructure, and Chinese Biomedical Literature Database. Risk of bias will be assessed according to the Cochrane Risk of Bias Tool. The Grading of Recommendations Assessment, Development and Evaluation system will be used to judge the overall quality of evidence supporting outcomes in this work. Data analysis was performed using Reviewer Manager 5.4. Results: The results of this systematic review will be published in a peer-reviewed journal. Conclusion: This systematic review will provide evidence to judge whether Janus kinase inhibitors is superior to leflunomide in patients with in rheumatoid arthritis.